Pengembangan Sistem Presensi Dosen dan Mahasiswa Menggunakan QR Code dengan Framework Codeigniter - Dadi Rosadi; Asep Ririh Riswaya; Dheni Apriantsani Budiman; Ricky Rohmanto (Ma'soem University, 2022)
Many technologies are constantly evolving to facilitate teaching and learning. The presence system became an obstacle in practicality and recording to a central server in STMIK Mardira Indonesia that has hundreds of students, especially if the presentation is done manually, requiring considerable time and providing opportunities for human error. System Presence Development Lecturer and Student using CodeIgniter Framework-based QR Code using the programming language PHP, JavaScript, jQuery. The method used, namely, observation, interview, literature, and systems development, is used using the model of requirements, analysis, design, implementation, and testing. It can be concluded that the system has been perfected following the schedule of lectures and the system can process data with both faculty and students.